2015
DOI: 10.1039/c5ra11559k
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids as buffer additives in ionic liquid-polyacrylamide gel electrophoresis separation of mixtures of low and high molecular weight proteins

Abstract: This study aims at investigating methodologies for better separation of proteins using novel hydrophobic ionic liquids (ILs). In this regard, hydrophobic ILs [C n PBr] (n ¼ 4, 6, 8) were synthesized and examined in ionic liquidpolyacrylamide gel electrophoresis (IL-PAGE) as buffer additives for separation of catalase (Cat), transferrin (Tf), bovine serum albumin (BSA), ovalbumin (Ova) and a-lactalbumin (a-Lact). The influence of alkyl chain length of the cation of these ILs and their concentration in running a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…The myoglobin adsorbs on the surface of BPG forming a stable monolayer. The biosensor developed could directly detect the concentration of oxygen in an aqueous solution with a detection limit of 2.3 × 10 −8 M. Hasan et al 366 exploited pyridinium-based ILs, viz. [C n PyrBr] (n = 4, 8), as buffer additive for high-resolution separation of low and high molecular weight proteins, including catalase, transferrin, BSA, ovalbumin, and α-lactalbumin, in IL-polyacrylamide gel electrophoresis as an alternative to the SDS-PAGE technique.…”
Section: Ionic Liquids As Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The myoglobin adsorbs on the surface of BPG forming a stable monolayer. The biosensor developed could directly detect the concentration of oxygen in an aqueous solution with a detection limit of 2.3 × 10 −8 M. Hasan et al 366 exploited pyridinium-based ILs, viz. [C n PyrBr] (n = 4, 8), as buffer additive for high-resolution separation of low and high molecular weight proteins, including catalase, transferrin, BSA, ovalbumin, and α-lactalbumin, in IL-polyacrylamide gel electrophoresis as an alternative to the SDS-PAGE technique.…”
Section: Ionic Liquids As Adjuvantsmentioning
confidence: 99%
“…Besides giving valuable information on the molecular mechanism of IL-protein interactions, the electrolytic nature of ILs as adjuvants has also been exploited for applications in oxygen sensing and IL-PAGE for the separation of proteins. , Ding et al reported that a direct electrochemical response of myoglobin could be observed for oxygen reduction from basal plane graphite (BPG) when [OHC 2 mim]­[BF 4 ] was used as a supporting electrolyte. The myoglobin adsorbs on the surface of BPG forming a stable monolayer.…”
Section: Ionic Liquid-protein Systemsmentioning
confidence: 99%
“…In gel-based sieving, the analyte migration is impeded . In comparison to electrophoresis in a slab gel, electrophoresis in a gel-filled capillary provides sharper peaks and better resolution of biopolymers in a shorter separation time. , The proteins separated by sieving are driven through the gel with a similar electrophoretic transport without any additive or by including a surfactant ,,,, or an ionic liquid , in the gel to bind to the proteins and cause them to have the same charge-to-size ratio. The proteins pass through the porous gel.…”
Section: Introductionmentioning
confidence: 99%